1990
DOI: 10.1002/neu.480210514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of castration and testosterone treatment on the activity of testosterone‐metabolizing enzymes in the brain of male and female zebra finches

Abstract: Recently, we described the distribution of testosterone-metabolizing enzymes (i.e., aromatase, 5 alpha- and 5 beta-reductases) in the zebra finch (Taeniopygia guttata) brain using a sensitive radioenzyme assay combined to the Palkovits punch method. A number of sex-differences in the activity of these enzymes were observed especially in nuclei of the song-control system. The hormonal controls of these differences have now been analyzed by gonadectomizing birds of both sexes and by giving them a replacement the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 59 publications
5
49
1
Order By: Relevance
“…Seasonal changes in AROM expression or activity in temperate birds might be modulated by the strong seasonal fluctuations in gonadal T secretion. In several bird species it has been shown that T up-regulates AROM activity and its expression in the preoptic area and anterior hypothalamus (Steimer and Hutchison, 1981;Schumacher and Balthazart, 1986;Vockel et al, 1990). The lack of seasonal changes in AROM expression despite the seasonal fluctuations in plasma T concentrations in male spotted antbirds suggests that in this species, AROM expression might be dissociated from circulating T. This might be an adaptive mechanism because it differs from what has been found in most studies on temperate birds.…”
Section: Ar Era and Arom Expression In Pommentioning
confidence: 80%
“…Seasonal changes in AROM expression or activity in temperate birds might be modulated by the strong seasonal fluctuations in gonadal T secretion. In several bird species it has been shown that T up-regulates AROM activity and its expression in the preoptic area and anterior hypothalamus (Steimer and Hutchison, 1981;Schumacher and Balthazart, 1986;Vockel et al, 1990). The lack of seasonal changes in AROM expression despite the seasonal fluctuations in plasma T concentrations in male spotted antbirds suggests that in this species, AROM expression might be dissociated from circulating T. This might be an adaptive mechanism because it differs from what has been found in most studies on temperate birds.…”
Section: Ar Era and Arom Expression In Pommentioning
confidence: 80%
“…To test for the neurosteroid specificity of estradiol effects on auditory processing, a separate group of birds (n = 3) was tested with retrodialysis of the nonaromatizable androgen 5β-DHT, with experimental procedures as above for aCSF pretreatment and stimuli playback. Similar to aromatase, the enzyme that synthesizes 5β-DHT from testosterone (5β-reductase) is expressed throughout zebra finch telencephalon (14,41).…”
Section: Methodsmentioning
confidence: 99%
“…Aromatase was initially characterized in the ovary and then detected in multiple areas of the basal forebrain in mammals (Naftolin et al, 1971(Naftolin et al, ,1972, raising the hypothesis that some effects of gonadal T on sexual and aggressive behavior are dependent upon local conversion of T to E 2 by brain aromatase. Indeed, a variety of data now show that brain aromatase is a key mediator of the link between T and behavior, and research on birds has provided seminal insights into 1) the cellular localization of aromatase protein and mRNA in neurons (Balthazart et al, 1990c;Shen et al, 1994), 2) the presence of aromatase at the synapse (Schlinger and Callard, 1989;Peterson et al, submitted), 3) hippocampal aromatase expression (Vockel et al, 1990;Saldanha et al, 2000), 4) the expression of aromatase in glia , 5) the regulation of aromatase by endocrine and environmental factors (Hutchison et al, 1986;Balthazart et al, 1990a;Schlinger and Callard, 1990), and 6) behavioral functions of aromatase (Adkins 1975;Adkins and Nock, 1976;Schumacher et al, 1984; and see first section).…”
Section: Aromatasementioning
confidence: 99%
“…The accompanying rise in circulating T coordinates a variety of processes in the brain, many of which require that T be aromatized to E 2 . These include, but are not limited to, increased expression of neuropeptides (e.g., AVT within the BSTm-LS system) (Viglietti- Panzica et al, 2001;Plumari et al, 2004), dramatic restructuring and growth of telencephalic song nuclei (Tramontin & Brenowitz, 2000;Nottebohm, 2004), and an increase in aromatase activity within the VMH and POA (Vockel et al, 1990).…”
Section: Multi-system Integration: Birdsong and Neuroendocrine Cascadesmentioning
confidence: 99%